Determining competitive advantage: The analytic hierarchy process - Korsakiene, Renata (Journal of Business Economics and Management, 2004)
Fundamental changes initiated by globalisation, new technologies, intensive competition, fluctuating demand of consumers, as well as economical and political changes encourage managers to be pro‐active, take greater risks and choose innovative strategies. Besides that, a company's ability to gain competitive advantage becomes an urgent problem. However, the managers lack a clear approach to the determination of competitive advantage. That is why the article analyses some important aspects concerning company's competitive advantage and presents the results of the determination of company's competitive advantage by using analytic hierarchy process.First Published Online: 14 Oct 2010